Katalog Digital Bangunan Komersial Sebagai Media Promosi Berbasis Augmented Reality - Dijaya, Rohman; Hibatullah Putra, Dimas Radito; Eviyanti, Ade; Taurusta, Cindy (Indonesian Journal Publisher, 2024)
Many building promotion techniques use building miniatures, but this media is less interactive. Augmented reality is a technology that allows interaction between the real and virtual worlds. To assist promotional activities, it is necessary to develop commercial building promotional media using the application